Reproductive immunology - Mor, Gil (Henry Stewart Talks, 2020)
Immunology of pregnancy, Interaction between the immune system and the fetus, Pregnancy is a unique immunological condition, Graft vs. tumor immunology, Immune cells in pregnancy, Differential cytokine profile according to the pregnancy stage, Inflammation and pregnancy, Implantation and inflammation, Pregnancy is a unique microbial condition, Bacteria and pregnancy: new paradigms